Symfony and Laravel – a comparative analysis of PHP programming frameworks - Krzysztof Kuflewski; Mariusz Dzieńkowski (Journal of Computer Sciences Institute, 2021)
This paper is a comparative analysis of PHP programming frameworks - Symfony and Laravel. The analysis was conducted on two test applications prepared for this purpose, based on the latest versions of the following technologies: Symfony 5.2 and Laravel 8. Both applications, being simple auction systems, have the same set of functionalities. They were compared in terms of selected criteria. Their implementation process, software metrics, performance and amount of community support were compared. Apache jMeter was used for performance testing. With its help, tests of several operations on databases were performed. The operations were as follows: adding auctions, retrieving auction details, editing, deleting auctions, bidding on an auction and simultaneous closing 1,000 auctions. The test results for the selected criteria were significantly better for the Laravel framework based application.